In vivo measurements to estimate culture status and neutral lipid accumulation in Nannochloropsis oculata CCALA 978: implications for biodiesel oil studies - Bongiovani, Natalia Soledad (2013)
The development of efficient, rapid and species-specific techniques is indispensable for assessing growth and neutral lipid yield in microalga cultures for biodiesel oil production. Nannochloropsis oculata is a small microalgae with a thick cell wall. In vivo techniques to estimate cell density, chlorophyll a and neutral lipids are reported. A calibration curve of cell density versus optical density was obtained and validated at 540 nm, under different growth phases. Intracellular neutral lipid storage was evaluated with fluorometry and epifluorescent microscopy employing fluorochrome Nile Red. The addition of 5% dimethyl sulfoxide enhanced 12.5 times the fluorescence signal efficiency. In situ fluorescence measurements allowed estimating the neutral lipid content (NR-FI). Besides, no significant differences were found in the lipid neutral content between gravimetric and triolein methods. The relationship between NR-FI and chlorophyll fluorescence signals was used as a neutral lipid accumulation index, which is useful in order to establish the optimum harvesting time. Thus, these procedures may be applied for a better monitoring mode of growth and neutral lipid accumulation in N. oculata's cultures at commercial scale.